PERAN OTORITAS JASA KEUANGAN DALAM PENGAWASAN PERBANKAN UNTUK MENCEGAH TINDAK PIDANA KORUPSI DI PT. BANK SUMUT (Studi : Putusan Tipikor Pengadilan Negeri Medan No. 93/Pid.Sus-TPK/2016/PN.Mdn. Jo. Putusan Pengadilan Tinggi Medan No. 06/Pid.Sus-TPK/2017/PN - Muhammad Firdaus; Bismar Nasution; Sunarmi Sunarmi; Muhammad Ekaputra (USU LAW JOURNAL, 2018)
ABSTRACT Cases of banking crime, not just criminal acts that occurred in the banking sector, apparently against the government banks including PT. Bank Sumut as a Regional Owned Enterprise (BUMD) of North Sumatera Province and Sub-Province / Municipality under it, incorporated as Limited Liability Company (PT) can also be investigated and investigation of alleged corruption. However, who is entitled to conduct such alleged corruption investigation in PT. Bank of North Sumatra, whether the Indonesian Police, the Attorney General, Corruption Eradication Commission, or OJK itself? Even if it is true ("quad non"), OJK has the right and authority to investigate and investigate alleged corruption in BUMN and BUMD, there is overlapping of rules, where OJK also has the authority to supervise and prevent fraud, the other hand the OJK shall be entitled and authorized to conduct investigations and investigation of alleged corruption in the bank. However, OJK should only have the authority to conduct an investigation of banking crime in the financial services sector.   Keywords          :     The Role of the Financial Services Authority; Banking Supervision; and Prevention of Corruption at PT. Bank of North Sumatra.